Propuesta de estrategia para la gestión del proceso del servicio de soporte y mantenimiento de las aplicaciones para los clientes de una empresa de desarrollo de software - González-Salas, Michael (Instituto Tecnológico de Costa Rica., 2014)
The Costa Rican company dedicated to the implementation of technological solutions, mainly in the financial sector, has the challenge of sustaining its growth in an efficient and effective way. For this, it is necessary that they have the processes aligned with the organization's strategy and that justify each one of the activities that today performs.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2014.
Keywords: Information Techonology Infraestructure Library; Metodología; Diseño; Procesos productivos